Optimization of UAE-NADES green extraction of bioactive compounds from chickpea (Cicer arietinum L.) sprouts using simplex lattice mixture design methodology - Waseem Khalid; Hyrije Koraqi; Imed E Benmebarek; Andrés Moreno; Tawfiq Alsulami; Robert Mugabi; Gulzar Ahmad Nayik (Ultrasonics Sonochemistry)
In the present study, a statistical tool called the simplex lattice mixture design method was used to create a new formulation of Natural Deep Eutectic Solvent (NADES), which is derived from a combination of three compounds (citric acid, glycerol, and water) to extract bioactive compounds from chickpea (Cicer arietinum L.) sprouts. The mixture (natural deep eutectic solvent) was formulated by combining three solvents including citric acid, glycerol, and water. The extraction was performed in a sonication bath for 30 min. The simultaneous optimization was performed to obtain the highest total polyphenol content (TPC), total flavonoid content (TFC) and antioxidants activity. The highest values of total polyphenol content (TPC), total flavonoid content (TFC) and antioxidant activity were 128.0 ± 0.2  mg GAE/100 g, 38.61 ± 0.03 mg CE/100 g and 2117 ± 1.8 µmol TE/100 g respectively. HPLC-DAD of the optimized extract was utilized for quantification of polyphenol compounds showing catechin as the main compound followed by chlorogenic acid, epicatechin, syringic acid, rutin, gallic acid, kaempferol 3-glucoside, ferulic acid, and coumaric acid. These findings may represent a significant advancement in the management of phenolic compound extraction for targeted uses, such as serving as alternatives to traditional antioxidants primarily employed in the food industry to improve nutritional quality. Furthermore, our research has shown that mixture designs are an efficient and useful method for structuring and optimizing experimental parameters to achieve the most accurate results with the minimum number of experiments.